Greece : Second Review Under the Stand-By Arrangement; Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Greece. (IMF Staff Country Reports; Country Report ;, 2010)
A very ambitious fiscal adjustment effort is under way. Fiscal institutional and sectoral reforms have been elaborated for a more durable adjustment. Greece's determination toward a comprehensive modernization of the health sector, beginning with a far-reaching reform of state enterprises and redoubling efforts to improve tax administration, is commended. An acceleration of reforms is essential to restore robust economic growth. Liquidity remains precariously tight. Pressure points are evident in the public sector, and still generally unfavorable investor sentiments suggest that the program is still at crossroads.